PENINGKATAN PENDAPATAN PETANI LADA MELALUI PERBAIKAN SISTEM USAHATANI - DEWI SAHARA; YUSUF -; SUHARDI - (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
The research on increasing farmer’s income thorough repairing pepper farmingsistem had done on November to December 2003 in Mowila and Lakomea villages,Landono sub district, Kendari regency, Southeast Sulawesi. The research aimed to knowfarmer’s income degree who repaired their farming sistem with integrated farming sistemcompared farmer’s income who used monoculture sistem so that to obtain description ofdifferent degree of income. The research was survey method and direct interviewed to 14farmers who integrated pepper with goat livestock and 16 farmers who had monoculturesistem. The result showed that pepper productivity on integrated farming sistem reached622,30 kg/ha while monoculture reached 242,85 kg/ha or 156,63 % in different.Difference of production caused difference of income Rp 5.536.919,23 each year or 341,85% in different. Income contribution of goat livestock on pepper farming sistem was 27,18% of totally farmer’s income. Besides as added value, goat livestock can also as a sourceof organic matter and could 50, 54 % production cost of total production economically.Therefore, to sustainability of pepper farming sistem and to emphasize production cost,raise goat livestock insentivelly near pepper area can be done.